Why not Liquefied Petroleum Gas? 4A Matrix of Energy Choice among Urban Below Poverty Line Households in India - Das, Satyasiba; Pal, Suchitra (International Journal of Energy Economics and Policy, 2019)
Liquefied petroleum gas (LPG) is one of the cleanest sources of fuel for urban below poverty line (BPL) households and households of urban BPL group are shifting from traditional cooking fuels to cleaner energy use. However, providing cleaner sources of cooking fuel to its urban BPL households has become one of the biggest challenges for developing countries. This paper reported on a recent survey on the household energy consumption pattern of urban (BPL) families living in the slums of Bhubaneswar, Odisha, India. The present study developed a 4A's matrix (Affordability, Availability, Awareness, and Attitude) to evaluate the different reasons behind acceptance and non-acceptance of LPG among the respondents. The results indicate that the 4 A's do not function in silos; rather they create a cumulative effect by working alongside of each other. Keywords: Liquefied Petroleum Gas, Below Poverty Line, Energy Consumption JEL Classifications: P28, I38, R22 DOI: https://doi.org/10.32479/ijeep.7586